2019
DOI: 10.1021/acsami.9b16499
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Engineered Electroforming-Free Analog HfOx Memristor and Its Application to the Neural Network

Abstract: The thin-film growth conditions in a plasma-enhanced atomic layer deposition for the (3.0–4.5) nm thick HfO2 film were optimized to use the film as the resistive switching element in a neuromorphic circuit. The film was intended to be used as a feasible synapse with analog-type conductance-tuning capability. The 4.5 nm thick HfO2 films on both conventional TiN and a new RuO2 bottom electrode required the electroforming process for them to operate as a feasible resistive switching memory, which was the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…Oxides of valve metals have shown remarkable performances as memristive elements. 15 18 Studies on Hf- and Ta-based memristors reported excellent electrical and memory properties, such as multilevel switching, high endurance, and data retention. 16 , 17 The deposition of oxide layers is commonly done by atomic layer deposition 19 , 20 or sputtering.…”
mentioning
confidence: 99%
“…Oxides of valve metals have shown remarkable performances as memristive elements. 15 18 Studies on Hf- and Ta-based memristors reported excellent electrical and memory properties, such as multilevel switching, high endurance, and data retention. 16 , 17 The deposition of oxide layers is commonly done by atomic layer deposition 19 , 20 or sputtering.…”
mentioning
confidence: 99%
“…[ 115 ] Kim et al realized the electroforming‐free device of Pt/Ta/HfO 2 /RuO 2 /Pt by thinning the HfO 2 film down to 3.0 nm, which increased the repeatability and uniformity of the switching performance. [ 116 ] Choi et al demonstrated a single‐crystalline SiGe epitaxial device with minimal cycle‐to‐cycle/device‐to‐device variations. [ 117 ] They utilized defect‐selective etching before electroforming to widen the dislocations providing preferential diffusion paths.…”
Section: Artificial Synapsesmentioning
confidence: 99%
“…These training processes keep repeating until the degree of error is scarcely noticed between the input images and the result in the last layer. Once training is completed, the neural network can work on its own 12 …”
Section: Introductionmentioning
confidence: 99%